Reactivation of Intestinal Inflammation Is Suppressed by Catestatin in a Murine Model of Colitis via M1 Macrophages and Not the Gut Microbiota - Rabbi, Mohammad F.; Eissa, Nour; Munyaka, Peris M.; Kermarrec, Laëtitia; Elgazzar, Omar; Khafipour, Ehsan; Bernstein, Charles N.; Ghia, Jean Eric (Frontiers in Immunology, 2017)
While there is growing awareness of a relationship between chromogranin-A (CHGA) and susceptibility to inflammatory conditions, the role of human catestatin (hCTS; CHGA352-67) in the natural history of established inflammatory bowel disease (IBD) is not known. Recently, using two different experimental models, we demonstrated that hCTS-treated mice develop less severe acute colitis. We have also shown the implication of the macrophages in this effect. The aims of this study were to determine (1) whether hCTS treatment could attenuate the reactivation of inflammation in adult mice with previously established chronic colitis; (2) whether this effect is mediated through macrophages or the gut microbiota. Quiescent colitis was induced in 7–8-week-old C57BL6 mice using four cycles (2%–4%) of dextran sulfate sodium (DSS). hCTS (1.5 mg/kg/day) treatment or vehicle started two days before the last induction of colitis and continuing for seven days. At sacrifice, macro- and microscopic scores were determined. Colonic pro-inflammatory cytokines (IL-6, IL-1, and TNF-), anti-inflammatory cytokines (IL-10, TGF-), classically activated (M1) (iNOS, Mcp1), alternatively activated (M2) (Ym1, Arg1) macrophages markers, were studied using ELISA and/or RT-qPCR. In vitro, peritoneal macrophages isolated from naïve mice and treated with hCTS (10-5 M, 12 h) were exposed to either lipopolysaccharide (LPS,100 ng/ml, 12 h) to polarize M1 macrophages or to IL-4/IL-13 (20 ng/ml) to polarize M2 macrophages. M1/M2 macrophage markers along with cytokine gene expression were determined using RT-qPCR. Feces and mucosa-associated microbiota (MAM) samples were collected, and the V4 region of 16s rRNA was sequenced. Micro- and macroscopic scores, colonic IL-6, IL-1, and TNF-), and M1 macrophages markers were significantly decreased in the hCTS treated group. Treatment did not have any effect colonic IL-10, TGF-, M2 markers nor modified the bacterial richness, diversity or the major phyla in colitic fecal and MAM samples. In vitro, pro-inflammatory cytokines levels, as well as their gene expression, were significantly reduced in hCTS-treated M1 macrophages. hCTS treatment did not affect M2 macrophage markers. These findings suggest that hCTS treatment attenuates the severity of inflammatory relapse through the modulation of the M1 macrophages and the release of pro-inflammatory cytokines.